PRE-CLASS TUTORIAL (PCT): LEARNING STRATEGIES TO IMPROVE STUDENTS' UNDERSTANDING OF THE P–V–T DIAGRAM ON THERMODYNAMICS - yustiandi, Yustiandi; Saepuzaman, Duden (UIN Sunan Gunung Djati Bandung, 2022)
This research was motivated by students' difficulties drawing and interpreting P-V-T diagrams to describe thermal processes and the ideal gas cycle. The method used in this study is a quasi-experimental method by comparing the results of the students' pre-test and post-test. This research was conducted on 21 students in one of the public schools in Pandeglang, Banten. Based on the study's results, PCT improved students' understanding of drawing and interpreting P-V-T diagrams to describe thermal processes and the ideal gas cycle. Several conceptual difficulties founded during the research. First, the most difficult in P-V, P-T, and V-T diagrams, respectively, is to draw the adiabatic process. Second, the percentage of students who answered the P-V diagram correctly was higher than those who answered the P-T and V-T diagrams. Third, students were more interested in and understood processes with unique characteristics such as isobaric, which means constant pressure; isochoric, which means constant volume and isothermal, which means constant temperature.